A Study on the Relationship between the Performance Characteristics and the Body Mass Index of 8-10 Year-Old Children - Ayan, Vedat (Asian Journal of Education and Training, 2018)
The study was carried out to discover the relationship between the performance characteristics (20 m. running, vertical jump, standing long jump, ball throwing, shuttle run) and the body mass index of 8-10 year-old school children. 3772 children (1995 male and 1777 female) aged 8-10 from Ankara participated in the study voluntarily. To measure the height of the children a stadiometer with ± 1mm graduation (Holtain, UK) and to measure their weight a stand art medical scale with ± 0.1kg readability were used. After the height and weight measurements, body mass indexes (BMI) of the children were calculated. Then, 20 m. running, vertical jump, standing long jump, ball throwing, shuttle run tests were applied to the children. To compare the mean values and to determine the differences between the groups T Test was applied and statistical correlation analysis was done to study the relationship between the Body Mass Index (BMI) and the Performance Characteristics(20 m. running, vertical jump, standing long jump, ball throwing, shuttle run). A statistically meaningful difference was defined between the female and the male participants when their mean points in body weight and height, body mass index, vertical jump, standing long jump, 20 m. run, ball throwing, and shuttle run(p<0.05) compared. In this comparison, while the average points of the male children in body weight and height, body mass index, vertical jump, standing long jump, ball throwing, and shuttle run were higher, their average points in 20 m. run were lower than the female children. It was observed that there was a relationship at a meaningful level and with a negative tendency between the points of body mass index of the male and female children and their vertical jump(r=-0.046, p<0.01), and standing long jump(r=-0.046, p<0.01) and shuttle run points(r= -0.229, p< 0.01). As to the relationship between the body mass index and 20 m run(r= 0.094, p< 0.01) and ball throwing (r= 0.286, p< 0.01), it was meaningful with a positive tendency. In our study, it was determined that the male children had better results than the female children according to the test results related to the physical characteristics and performance measurements. It has been concluded that the differences found stem from the gender difference and depending upon the environmental and cultural factors at these ages, the male children are thought to have a better development in terms of performance characteristics.